Asuhan Keperawatan pada Tn.S dengan Gangguan Sistem Musculoskeletal; Fraktur Humerus Proksimal di Rumah Sakit Haji Adam Malik, Medan - Bungaria, Sri; Tanjung, Dudut; E, Edianto; Afriani, Dina; Hanim, Saodah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Background; Proximal humeral fractures (PHF) are one of the most common fractures in adults, with prevalence ranging from 4% to 10% of all fractures. These fractures are often caused by low energy trauma such as falls from a standing position or medical conditions such as osteoporosis. Treatment of PHF can be conservative or surgical, depending on the type and severity of the fracture. Untreated complications can lead to joint stiffness and worsen the patient's quality of life. Therefore, the role of nurses in supporting patient self-care is very important, especially in providing appropriate education and interventions. Objective; This study aims to provide nursing care to patients with PHF who experience immobilization. Methods: This study used a case report design that analyzed a 44-year-old male patient with a diagnosis of neglected proximal humeral fracture and metatarsal fracture. Nursing diagnoses found include acute pain, impaired physical mobilization, and impaired skin integrity. Interventions include pain management with analgesic administration, physical mobilization support, and skin integrity care. Results; The results of nursing planning showed increased physical mobility and pain reduction after 3x24 hours, as well as improved skin integrity after two meetings. Conclusion; This nursing care shows the importance of the nurse's role in providing education to patients and families to support post-fracture recovery.